Usapang babae gender awareness through theater arts, games and processes. (Manila National Commission on the Role of Filipino Women, 1992)
Theater for grassroots education. Basic workshop for gender awareness. Alternative and supplementary exercises. "This is primarily a manual for gender awareness facilitators who have undergone training in the use of theater games and processes and facilitator's adept in gender issues and theater techniques." It is a workshop book with modules in scheduled sessions.
Contents: Grassroots education. Workshop for gender awareness alternative and supplementary exercises.
Purpose: It is a part of our commitment to advocate gender and our contribution to people in constant communication with others; a guide for trainors and extension workers.
UCWS-2014-G-1950 donated by Jenny Llaguno.
Keywords: Women's studies -- Handbooks, manuals, etc. -- Philippines; Gender identity; Sex role -- Handbooks, manuals, etc. -- Philippines